PATHOPSYCHOLOGICAL FEATURES OF COMORBID ALCOHOLISM AND SCHIZOAFFECTIVE DISORDERS (World Bulletin of Public Health, 2024)
Researchers have emphasized the close interrelationship of factors that determine the occurrence and development of mental illness for persons with comorbid forms of drug-related disorders. Meanwhile, the combination of alcohol addiction with schizophrenia contributes to an increase in the number of socially dangerous actions.
Keywords: alcoholism; schizoaffective disorders; comorbidity